ANALISIS RASIO PROFITABILITAS DAN RASIO SOLVABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Purba, Herli Mersi; L. Tobing, Vargo Christian (SCIENTIA JOURNAL, 2021)
Changes in stock prices are a very important factor in determining the purchase and sale of shares from an investment activity in the capital market. The share price is a reflection of the state of the company because it must be taken into account by investors in investing. The price of the shares is determined by the supply and demand relationship in the capital market. This study aims to study the impact of profitability ratios and solvency ratios on the stock prices of manufacturing companies in the food and beverage sub-industry listed on the Indonesia Stock Exchange from 2016 to 2020. The benchmark of each variable is ROA as a measure of profitability, DER as a measure of solvency. The study method uses quantitative methods. The technique in determining the sample uses intentional sampling. In this study, the population consists of 32 companies and 14 companies as samples. The research condemns the secondary data types in the form of financial statements obtained from IDX. The data analysis method of this study adopts multiple linear analysis, and is processed by SPSS 25 version. According to the test results, it is shown that part of the profitability has a significant impact on the stock price is not significant. At the same time, profitability and solvency have a significant impact on stock prices. Keywords: profitability; solvability; stock price.